MANAJEMEN PERGURUAN TINGGI BERBASIS NILAI-NILAI PESANTREN (Kajian Pemikiran Alternatif) - Mardiyah, - - (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
Pathology bureaucracy syndrome that continues toinfect the world of education in Indonesia resulted in theformulation of management education does not find appropriateand relevant in the midst of poor quality and the quality ofeducation. Proven innovation and improvement efforts as wellas the management education system ranging from educationdecentralization and school autonomy and school-basedmanagement (SBM), which have been initiated by thegovernment was unable so far to increase the quality of nationaleducation. Finally, it happens competitiveness of our educationaloutput relatively weak compared to other countries. Planning toconvert the values of the pesantren as theology and basemanagement alternative education course departed from thepresence of 'deadlock' national education system to print thehuman resources quality as a result of the multidimensionalcrisis has hit Indonesia. The moral and identity crises thatcontinue to color the behavior of the nation's elite in particularand the whole society in general have attacked them. Withvalues based boarding school, it is expected that the principles ofstruggles, devotion, sacrifice, jihad, ijtihad, and Mujahadahinspired by the values of sincerity, simplicity, confidence andindependence, brotherhood and togetherness as well as thefreedom to think positive and productive be the mainstay ofmanagement education and development of various types ofeducation that is managed in it.Keywords: bureaucracy, decentralization, pesantren